ANALISIS PERENCANAAN PAJAK MELALUI REVALUASI ASET TETAP PADA PT DESTINASI TIRTA NUSANTARA TBK - Yohanes Demu; Ignasia Bunga Andrada (Universitas Nusa Cendana, 2021)
ABSTRACT This study aims to determine the application of tax planning through fixed asset revaluation at PT Destinasi Tirta Nusantara Tbk. The research approach used is descriptive quantitative. The type of data used is quantitative data and qualitative data. Quantitative data includes data on fixed assets of the company, the annual financial statements of PT Destinasi Tirta Nusantara Tbk for 2016 and the qualitative data used is the company profile in the 2018 annual report of PT Destinasi Tirta Nusantara Tbk with secondary data sources taken through the official website of the Indonesia Stock Exchange. The analysis technique used is descriptive. The results of this study indicate that the application of tax planning through fixed asset revaluation has an impact on the increasing tax expense that must be paid by companies as corporate taxpayers. When companies pay final income tax on fixed asset revaluation, the amount of tax expense that must be paid by the company increases. This is due to revaluation that is only carried out on fixed assets on land where the fixed assets cannot be depreciated. PT Destinasi Tirta Nusantara Tbk needs to consider not only revaluing land fixed assets. PT Destinasi Tirta Nusantara Tbk can carry out revaluation of fixed assets other than land, which can be depreciated, such as buildings and infrastructures, furniture and fixtures, and vehicles. Keywords: Tax Planning, Fixed Asset Revaluation, Fixed Assets